Potential applications, limitations and future perspectives of cleaner production for sustainable manufacturing processes in Sri Lanka - A review. - Maheepala, S.A.D.S.S.; Jayasinghe, G.Y. (University of Jaffna, 2018)
Industrial sector performs a vital role in economic development of any country by providing different benefits such as earning foreign exchange, creating employment opportunities and developing regional infrastructures. After termination of thirty years of war, Sri Lanka achieved high GDP growth and manufacturing sector is contributed to 32% of total GDP. Subsequent, industrial sector growth caused detrimental environmental issues which are generated by inappropriate manufacturing and maintenance practices. Raw material, labor hour and by products can be wasted during manufacturing processes which caused financial losses to the industry. Cleaner production concept is implemented as a technique which can be used for reducing any wastage and undesired conditions of manufacturing processes. It helps to maintain high productivity, appropriate functions in industries and high economic benefits for all stakeholders. Also, waste reduction helps to decrease environmental impacts, conserve limited natural resources and maintain the sustainability. Sri Lankan manufacturing sector has a high potential to apply cleaner production concept and it can be apply for any type of manufacturing processes from small scale to large scale. Sri Lanka has own cleaner production center which facilitate for auditing and other services with skilled resource persons. Some limitations are accounted on applicability of cleaner production in Sri Lankan manufacturing sector and future developments are needed. The present study examines a comprehensive review on (i) cleaner production concept, (ii) its potential applications for manufacturing sector in Sri Lanka, (iii) limitations and (iv) future perspectives for developing this concept to achieve sustainability.
Keywords: Cleaner production; Sustainable development; Sustainable manufacturing process; Waste reduction